Recent infrared detector technologies, applications, trends and development of HgCdTe based cooled infrared focal plane arrays and their characterization - Bhan, R.K.; Dhar, V. (Opto-Electronics Review, 2019)
Infrared thermal imaging, using cooled and uncooled detectors, is continuously gaining attention because of its wide military and civilian applications. Futuristic requirements of high temperature operation, multispectral imaging, lower cost, higher resolution (using pixels) etc. are driving continuous developments in the field. Although there are good reviews in the literature by Rogalski [1–4], Martyniuk et al. [5] and Rogalski et al. [6] on various types of infrared detectors and technologies, this paper focuses on some of the important recent trends and diverse applications in this field and discusses some important fundamentals of these detectors.